Assessment of Drug Related Problems among Type 2 Diabetes Mellitus Patients with Hypertension in Doloksanggul Hospital, North Sumatera: A Retro prospective Study - Purba, Eva Dewi; M, Khairunnisa; Anjelisa, Hasibuan Poppy (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: The aim of this study was to assess the drug-related problems (DRPs) in Type 2 diabetes mellitus(T2DM) patients whom also diagnosed with hypertension. Methods: The retrospective study was conducted from October to December 2018 at Doloksanggul Hospital in North Sumatera, Indonesia involving 42 T2DM with hypertension patients according to research inclusion criteria. The assessment of DRPs was based on the Pharmaceutical Care Network Europe (PCNE) tools version 8.01. Results: This study identified 41 DRPs, averaging 0.98±0.24 DRPs per patient. The majority of problems were treatment effectiveness problems 97.62% (41 patients) while the patient related was the main causes (47.24%). The most intervention was conducted at patient level (71.62%).Conclusion: Early detection of DRPs by pharmacist are essential to prevent DRPs and to ensure the effectiveness of drug therapy.